Evaluación del número de comederos por hectárea utilizados para la alimentación de camarones litopenaeus vannamei - Napa Zambrano, Blasco Otilio (2010)
The present investigation was carried to Evaluate the number of troughs for more convenient hectare for the feeding of the shrimp, applying three treatments of fifteen, twenty and thirty troughs for hectare feeding once and twice a day, the study was carried in the camaronera "PescaMar" of property of Mr. Ernesto Pesantes Orellana, located in the place Guarumal, of the Machala city, province de El Oro. The field work had duration of five months, beginning in September of the 2009, concluding in January of the 2010. The three treatments of fifteen, twenty and thirty troughs for hectare feeding once and twice a day, they were used from the second week of cultivation until the end of the same one. In analyzing the weight gain versus the number of feeders was determined that this convenience when feeding uses thirty per hectare, because the final analysis reports an average of 0.93 g. , because the final analysis reports an average of 19.95 g. In terms of feed conversion, best results were using feeding thirty per hectare, with an average of 1.97 but with a survival rate of 55%. When analyzing survival versus the number of feeders is determined that the best was fed with 15 feeders per hectare with an average of 66%. When analyzing food consumption versus the number of feeders was determined that the convenience that when using feeders twenty per hectare because the analysis reports an average of 3 220 pounds. In analyzing the pounds harvested per hectare versus the number of feeders was determined that this convenience when feeding uses thirty per hectare, because the final analysis reports an average of 2 573.20 lbs. 87 According to economic performance treatment for thirty hectares feeders, feeding one times per day, which has generated more useful.